The effect of rapid weight loss on the handgrip strength of national-level wrestlers - Carlo Rossi; Roberto Roklicer; Antonino Bianco; Marko Manojlovic; Barbara Gilic; Tatjana Trivic; Patrik Drid (Annales Kinesiologiae, 2022)
The effects of rapid weight loss (RWL) in combat sports athletes is an area that is not yet fully discovered. Therefore, the goal of this study was to determine the impact of weight loss on HGS (handgrip strength) in Greco-Roman wrestlers.